2022
DOI: 10.3390/s22135027
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Identifies Chronic Low Back Pain Patients from an Instrumented Trunk Bending and Return Test

Abstract: Nowadays, the better assessment of low back pain (LBP) is an important challenge, as it is the leading musculoskeletal condition worldwide in terms of years of disability. The objective of this study was to evaluate the relevance of various machine learning (ML) algorithms and Sample Entropy (SampEn), which assesses the complexity of motion variability in identifying the condition of low back pain. Twenty chronic low-back pain (CLBP) patients and 20 healthy non-LBP participants performed 1-min repetitive bendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, our study diverges by offering a broader analysis with three different functional exercises (flex, tot, and lat. ), expanding the scope beyond our singular exercise focus [35]. Our study builds upon the work of De la Torre et al, whose research involves a performance comparison of classification algorithms for MoCap triaxial movement exercises, while their emphasis is on cervical assessment, our study focuses specifically on the lumbar region.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study diverges by offering a broader analysis with three different functional exercises (flex, tot, and lat. ), expanding the scope beyond our singular exercise focus [35]. Our study builds upon the work of De la Torre et al, whose research involves a performance comparison of classification algorithms for MoCap triaxial movement exercises, while their emphasis is on cervical assessment, our study focuses specifically on the lumbar region.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted with 38 acute and subacute non-specific neck pain patients and 42 healthy control participants and demonstrates that machine-learning methods can provide relevant information from relatively small datasets. The same observation is made in [ 10 ], where the kinematics of 20 patients with chronic low-back pain (CLBP) and 20 healthy participants without CLBP were recorded from three IMUs attached to the participants while they performed 1-min repetitive bending (flexion) and return (extension) trunk movements. It was found that Gaussian Naive Bayes machine learning achieved 79% accuracy in identifying CLBP patients.…”
mentioning
confidence: 81%
“…In a previous study [16], the proposed GNB machine learning model predicted the risk of chronic LBP. General characteristics, including sex, age, BMI, and physical activity level, were collected from all participants using the Global Physical Activity Questionnaire.…”
Section: Literature Reviewmentioning
confidence: 99%